2014
DOI: 10.1152/advan.00024.2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of learning styles of undergraduate medical students using the VARK questionnaire and the influence of sex and academic performance

Abstract: While there are several tools to study learning styles of students, the visual-aural-read/write-kinesthetic (VARK) questionnaire is a simple, freely available, easy to administer tool that encourages students to describe their behavior in a manner they can identify with and accept. The aim is to understand the preferred sensory modality (or modalities) of students for learning. Teachers can use this knowledge to facilitate student learning. Moreover, students themselves can use this knowledge to change their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
104
2
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 10 publications
19
104
2
13
Order By: Relevance
“…Findings of the study further elaborate that, the majority (89%) of the students perform the multimodal learning style, which is a collection of learning styles such as Bimodal, Trimodal and Quadrimodal) rather than one single learning style (Unimodal).Similarly, these results agree with the findings of the other studies (Zeynep&Melis, 2007;Urval et al, 2014;Kanchi et al, 2013;Loulwa, 2013;Turky& Almigbal, 2015) among medical science undergraduates. Victor (2011) did a similar study among the students at the Faculty of Science and Agriculture, the University of the West Indies and concluded that most of the students show similar characteristics as depicted in the above studies.…”
Section: Learning Stylessupporting
confidence: 89%
See 1 more Smart Citation
“…Findings of the study further elaborate that, the majority (89%) of the students perform the multimodal learning style, which is a collection of learning styles such as Bimodal, Trimodal and Quadrimodal) rather than one single learning style (Unimodal).Similarly, these results agree with the findings of the other studies (Zeynep&Melis, 2007;Urval et al, 2014;Kanchi et al, 2013;Loulwa, 2013;Turky& Almigbal, 2015) among medical science undergraduates. Victor (2011) did a similar study among the students at the Faculty of Science and Agriculture, the University of the West Indies and concluded that most of the students show similar characteristics as depicted in the above studies.…”
Section: Learning Stylessupporting
confidence: 89%
“…This study supports most of the arguments that gender has no significant influence on learning styles (Zeynep&Melis, 2007;Urval et al, 2014;Loulwa, 2013;Victor, 2011;Turky&Almigbal, 2015).…”
Section: Influence Of Gender On Major Learning Stylessupporting
confidence: 88%
“…Urval et al [8] and Nayak et al [9] in their study reported multimodality (68.7%) as the preferred mode where as our study reported unimodality as the preferred one. Similar report as our study was given by Baykan and Naçar.…”
Section: Discussionsupporting
confidence: 65%
“…the presentation of hypothetical anatomical models in the course of Anatomy) to them (Mohammadi et al, 2015). In studies conducted on Turkish medical students (Baykan & Naçar, 2007) and on students at Michigan University (Urval et al, 2014), most students preferred multiple learning styles. It must be noted that one of the features of effective learning is having the ability to apply multiple learning styles and strategies in different learning situations.…”
Section: Discussionmentioning
confidence: 99%